Effects of lipopolysaccharide on the histomorphology and expression of toll-like receptor 4 in the chicken trachea and lung. Issue 5 (2nd September 2016) - Ansari, Abdur Rahman; Ge, Xiao-Hong; Huang, Hai-Bo; Huang, Xi-Yao; Zhao, Xing; Peng, Ke-Mei; Zhong, Ju-Ming; Liu, Hua-Zhen
ABSTRACT: Endotoxin or lipopolysaccharide (LPS) exposure can cause injury to the respiratory airways and in response, the respiratory epithelia express toll-like receptors (TLRs) in many species. However, its role in the innate immunity in the avian respiratory system is poorly understood. The aim of the present study was to evaluate the effects of LPS on the chicken trachea and lung. After intraperitoneal LPS or saline injection, the trachea and lungs were harvested at 0, 12, 36 and 72 h ( n  = 6 at each time point) and histopathologically analysed using haematoxylin and eosin and periodic acid-Schiff staining, while TLR4 expression was determined by immunohistochemistry and secretory Immunoglobulin A (SIgA) levels by enzyme-linked immunosorbent assay. After LPS stimulation, we observed a remarkable decrease in the number of goblet cells along with obvious disruption and desquamation of the ciliated epithelium in the trachea, blurring of the boundary between pulmonary lobules, narrowed or indistinguishable lumen of the pulmonary atria and leukostasis in the lungs. Following LPS stimulation, TLR4 protein expression was up-regulated in both the trachea and the lungs and was found on the ciliated columnar cells as well as in the submucosa of the trachea, and in the lungs on parenchymal and immune cells. However, SIgA levels were only up-regulated in the trachea at 12 h following LPS stimulation. Hence, this report provides novel information about the effects of LPS on the microstructure of the lower respiratory tract and it is concluded that its intra-peritoneal administration leads to TLR4-mediated destruction of the tracheal epithelium and pulmonary inflammation along with increased SIgA expression in the tracheal mucosa.